SaLoRa, Inovasi Kearifan Lokal Kerang Endemik Madura dan Kelayakannya Sebagai Pesaing Saus Tiram Komersil - Natalia, Grace; William Oen, Shem; Key Setyawan, Fabian; Sudarko, Tirta (Inovbook, 2024)
Lorjuk (Solen spp.) is a species of clam that can be found within the shallow waters of Indonesia, it is located specifically in the Strait of Madura. Lorjuk has been a culinary staple for the people in the Surabaya and Madura regions. However, despite the widespread availability of processed lorjuk food products, a large amount of the population remains unfamiliar with the taste of lorjuk. Moreover, some individuals have yet to try processed lorjuk products. For this reason, the main objective of this research is to develop an innovative product from lorjuk branded as “Saus Lorjuk Nusantara (SaLoRa)” which will provide a palatable flavor profile. As a worthy product, SaLoRA is also ready to be compared with commercial flavor-enhancing condiments. The validity parameters of SaLoRa products in this study will be more focused on the acceptance of the public to the quality attributes of the sauce (color, flavor, aroma, and solidity), as well as the durability of the product in storage. Furthermore, the method of research will be chosen using a comparative qualitative approach, using descriptive and hedonic-type organoleptic tests. For the validity of the resistance, the research is conducted quantitatively using colorimetric tests to determine the product's life, as well as qualitative testing through organoleptic observations as information validity enhancers. The results indicate that SaLoRa has quality attributes that are not much different from commercial sausages, even the quality of the SaLo Ra flavor is superior and acceptable to the panels. While SaLoRa's lifespan at room temperature lasts for only 42 hours, it can be tested by storing it in a refrigerator at a temperature below 5°C.